Pour le meilleur et pour le pire ! Les arbres en ville peuvent-ils faire patrimoine ? Analyse des spatialités concurrentes arbres-riverains à Grenoble - Claire Tollis (Éditions en environnement VertigO, 2013)
Embracing urban trees as a heritage is challenging. We analysed over two thousand complaint letters sent to the City Parks Service in Grenoble (France) and we interviewed the people who received them. It appears that trees and inhabitants hardly get along. This cohabitation problem is inherently geographical : they are both bothered in sharing the same space. New management techniques that aim to “let nature be” build up on this issue. But we also found that sometimes inhabitants show “the tree for the forest” in the sense that other problems that “have nothing to do with trees” focus on them, while they are related to public relations. In this context, we intend to share the tricky process that tries to build urban trees as a heritage but has not succeeded yet in having them accepted for what they are : living things.